Valuation of Internet and technology stocks implications for investment analysis - Kettell, Brian (Oxford : Butterworth-Heinemann, 2002)
New ways of looking, researching and valuing these companies need to be addressed. Valuation of Internet and Technology Stocks offers practical information to enable institutional investors to value internet.coms and high tech companies more accurately. The author highlights the deficiencies in existing stock market techniques and shows how they need to be modified or, in most cases, replaced with techniques more suited for the revolution in economies which had taken place since 1991. The economic rules in the financial market place have changed to the extent that strategies successfully applied in the post war era have now been relegated to the deleted items box. 'Valuation on Internet and Technology Stocks' reviews existing stock market techniques highlighting their deficiencies and show how the New Economics necessitates new forms of investment analysis. * Investigates why there has been a high correlation between high loss companies and a rocketing stock price * Questions whether there is still a place for discounted cash flows when there is no cash flow to discount * Considers what new methods are available to value super growth companies and whether these methods are any better than existing techniques.
Preface: the collapse of technology/Internet stocks; The age of information and the democratization of data; The new economy: where do technology/Internet stocks fit in?; Technology and the Internet Economy: what made it all happen?; How do you value traditional common stocks?; Applying the Porter Model to the valuation of technology/Internet stocks; What are the problems with applying traditional valuation models for Technology/Internet stocks?; Bubblelogy, stock market and the technology/Internet stock price collapse; What do we know about the valuation of technology/Internet stocks (I)?; What do we know about the valuation of technology/Internet stocks (II)?; Derivative markets, real options and the valuation of technology/Internet stocks; What are the lessons for investors from the year 2000 collapse of technology/Internet stocks?; Bibliography and web site addresses.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Corporations -- Valuation; Internet -- Economic aspects; Technology -- Economic aspects; Electronic books